‘Shaken, but not stirred’: Sixty years of defining social innovation - Edwards-Schachter, Mónica; Wallace, Matthew (Technological Forecasting and Social Change, 2017)
This paper examines the evolution in the conceptualization of Social Innovation (SI) with a view to elucidating the multiplication of uses of the term over the last half century. We performed a comprehensive and systematic literature review extracting 252 definitions of SI through a search of 2,339 documents comprising academic papers, books and book chapters, together research and policy reports. To guide the inductive analysis of pluri-vocal discourses we assume innovation to be a learning-based process involving actors’ interactions and social practices. We apply mixed qualitative methodologies, combining content analysis based on an interpretivist ontology with cognitive mapping techniques. Our findings show that SI was introduced as an analytical concept by incipient academic communities and has spread in the last decades as a normative concept fuelled by development and innovation policies. SI is defined by a set of common core elements underpinning three different and interrelated discursive ‘areas’: processes of social change, sustainable development and the services sector. We point to some policy implications and a number of promising avenues for research towards the advancement of a broader socio-technical theory of innovation.
Keywords: Histoire

Social innovation: how societies find the power to change - Mulgan, Geoff (Policy Press, 2019)
The 21st century has brought a cornucopia of new knowledge and technologies. But there has been little progress in our ability to solve social problems using social innovation – the deliberate invention of new solutions to meet social needs - across the globe. Geoff Mulgan is a pioneer in the global field of social innovation. Building on his experience advising international governments, businesses and foundations, he explains how it provides answers to today’s global social, economic and sustainability issues. He argues for matching R&D in technology and science with a socially focused R&D and harnessing creative imagination on a larger scale than ever before. Weaving together history, ideas, policy and practice, he shows how social innovation is now coming of age, offering a comprehensive view of what can be done to solve the global social challenges we face.
Keywords: Définition; Histoire; Innovation sociale; Politiques; Réservé UdeM; Technologie

Theories of Social Innovation - Logue, Danielle (Edward Elgar, 2019)
As we grapple with how to respond to some of the world’s most pressing problems, such as inequality, poverty and climate change, there is growing global interest in ‘social innovation’ as a potential solution. But what exactly is ‘social innovation’? This book describes three ways to theorise social innovation when seeking to manage and organize for both social and economic progress.
Keywords: Australie; Histoire; Innovation sociale; Théorie Néo-Institutionnelle